Blind - Wiseman, Frederick; Davey, John (Frederick Wiseman - Intégrale Vol. 2: 1980-1994, 2016)
"Blind" shows the educational programs and daily life of students in kindergarten through the 12th grade at the Alabama School for the Blind. The School is organized around the effort to educate blind and visually impaired students to be in charge of their own lives. Sequences in the film include mobility training, braille instruction and orientation as well as traditional classroom subjects such as English, history, science and music. Other sequences show psychological counseling sessions; vocational training; staff dealing with student disciplinary problems; and the wide variety of recreational and athletic programs. [www.zipporah.com]